Terpinen-4-ol triggers autophagy activation and metacaspase-dependent apoptosis against Botrytis cinerea - Wang, Kunchun; Li, Zhenbo; Shen, Shengnan; Wang, Lei; Wang, Huizheng; Li, Delong (Frontiers in Microbiology, 2025)
Botrytis cinerea, a necrotrophic phytopathogen responsible for gray mold disease, poses a significant threat to global postharvest horticultural production due to substantial spoilage of fruits and vegetables. This study systematically investigated the antifungal efficacy and molecular mechanisms of terpinen-4-ol against B. cinerea. Terpinen-4-ol exhibited a broad-spectrum of antifungal activity, significantly inhibiting both mycelium growth and conidial viability of B. cinerea. Further analyses revealed that terpinen-4-ol disrupted cell membrane integrity and induced reactive oxygen species (ROS) accumulation. The inhibitory effect may be attributed to its ability to promote ROS accumulation and induce autophagy activity, thereby disrupting the intracellular redox balance and autophagic processes in fungi, ultimately leading to apoptosis via a metacaspase-dependent pathway. Altogether, these findings revealed a specific antifungal mechanism of terpinen-4-ol against B. cinerea, suggesting its potential as an effective preservative for postharvest preservation of fruits.